2021
DOI: 10.1002/ptr.7304
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective properties of ethanolic extract of Citrus unshiu Markovich peel through NADPH oxidase 2 inhibition in chemotherapy‐induced neuropathic pain animal model

Abstract: The present study aimed to determine the antioxidant effect of Citrus unshiu Markovich (CUM) extract in neuronal cell lines under oxidative stress and to investigate the effect of chemotherapy‐induced peripheral neuropathy (CIPN) on the nociceptive response in a preclinical mice model. We tested the inhibition of H2O2 in Neuro2A cells treated with CUM. Experimental animals were treated with oxaliplatin to induce CINP, and then administered oral CUM for 4 weeks in order to observe the effect of CUM. Animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, it has been shown that not only NO acts as a signaling molecule but that ROS- derived from NADPH oxidase- also has a regulatory function with associated signaling pathways [ 66 , 67 ]. It has been suggested that NADPH oxidase presents a higher hierarchy in the signaling of inflammatory circuits and that it controls the production of NO by modulating the expression of iNOS [ 67 , 68 , 69 , 70 ]. However, it has also been reported that iNOS activity is capable of regulating the function of the NADPH oxidase complex [ 71 , 72 ].…”
Section: Relationship Between No and Nadph Oxidasementioning
confidence: 99%
“…Furthermore, it has been shown that not only NO acts as a signaling molecule but that ROS- derived from NADPH oxidase- also has a regulatory function with associated signaling pathways [ 66 , 67 ]. It has been suggested that NADPH oxidase presents a higher hierarchy in the signaling of inflammatory circuits and that it controls the production of NO by modulating the expression of iNOS [ 67 , 68 , 69 , 70 ]. However, it has also been reported that iNOS activity is capable of regulating the function of the NADPH oxidase complex [ 71 , 72 ].…”
Section: Relationship Between No and Nadph Oxidasementioning
confidence: 99%
“…In this context, NADPH oxidases (NOXs), whose primary function is the regulated production of ROS [15], have emerged as potential pharmacological targets for NP, which is corroborated by mounting evidence implicating some NOX isoforms in NP development [3,16]. Specifically, NOX2 is upregulated in the nervous system after nerve injury [17][18][19][20][21][22], and NOX2-knockout mice exhibit attenuated NP behaviors [17,20,23,24]. Furthermore, NOX2-derived ROS are involved in spinal neuroimmune activation that underlies NP, namely microglia activation, and proinflammatory cytokine expression [17].…”
Section: Introductionmentioning
confidence: 95%
“…In particular, the therapeutic effects of the peel covering C. unshiu have received more attention than other parts of the plant, because it exerts outstanding antioxidant effects compared to the pulp owing to its high mineral composition [ 13 , 14 ]. C. unshiu peel is widely used as a therapeutic agent for clinical purposes, such as neuropathic pain [ 15 ], cervical cancer [ 16 ], nonalcoholic fatty liver [ 17 ], hyperglycemia [ 18 ], pancreatic cancer [ 19 ], and systemic inflammation [ 20 ]. This raw material can also be processed using various extraction protocols, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, water or ethanol extraction is a commonly used method to extract flavonoids from natural substances, hence, many studies employing solvent-extracted CUP have been conducted. For example, the ethanol derivative of CUP ameliorated oxidative stress by suppressing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 expression (NOX2) in a chemotherapy-induced neuropathic pain animal model [ 15 ] and decreasing the expression levels of pro-inflammatory cytokines, such as interleukin (IL)-6, interferon (IFN)-γ, and tumor necrosis factor-alpha (TNFα), in a type 2 diabetes and systemic inflammation mouse model [ 18 , 20 ]. Moreover, water extracts of CUP have been reported to attenuate dextran sulfate sodium-induced colitis by regulating the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway [ 21 ].…”
Section: Introductionmentioning
confidence: 99%